Le ‘mutazioni’ del territorio storico. Patrimonio ed economia creativa nella dimensione locale. Il caso sardo - Alessia Usai (Scienze del Territorio, 2017)
In Italy, the application of the organizational model of the traditional industrial district to the management of cultural heritage and activities has fostered the establishment and the diffusion of cultural districts throughout the country. Research conducted on Italian Regions, including Sardinia, have revealed the peculiarities of the organizational models that govern the sector of cultural heritage from protection to valorisation: the ability to generate ‘hybrid’ district forms linked to technological innovation, agribusiness and tourism, but even the weak emergence of advanced cultural districts and meta-districts as supra-local business conglomerates (creative and cultural clusters). Analysing the experiences of the Sulcis and Iglesiente areas in Sardinia, selected as case studies, the paper investigates the reasons and factors that influence and limit the affirmation of supra-local clusters in the valorisation of the historical territory, highlighting the contribution of urban planning to overcome them.